Genome-Wide Characterization of R2R3-MYB Transcription Factors in Pitaya Reveals a R2R3-MYB Repressor HuMYB1 Involved in Fruit Ripening through Regulation of Betalain Biosynthesis by Repressing Betalain Biosynthesis-Related Genes - Fangfang Xie; Qingzhu Hua; Canbin Chen; Zhike Zhang; Rong Zhang; Jietang Zhao; Guibing Hu; Jianye Chen; Yonghua Qin (Cells, 2021)
The MYB (myeloblastosis) superfamily constitutes one of the most abundant transcription factors (TFs) regulating various biological processes in plants. However, the molecular characteristics and functions of MYB TFs in pitaya remain unclear. To date, no genome-wide characterization analysis of this gene family has been conducted in the Cactaceae species. In this study, 105 R2R3-MYB members were identified from the genome data of Hylocereus undatus and their conserved motifs, physiological and biochemical characteristics, chromosome locations, synteny relationship, gene structure and phylogeny were further analyzed. Expression analyses suggested that three up-regulated HuMYBs and twenty-two down-regulated HuMYBs were probably involved in fruit ripening of pitaya. Phylogenetic analyses of R2R3-MYB repressors showed that seven HuMYBs (HuMYB1, HuMYB21, HuMYB48, HuMYB49, HuMYB72, HuMYB78 and HuMYB101) were in clades containing R2R3-MYB repressors. HuMYB1 and HuMYB21 were significantly down-regulated with the betalain accumulation during fruit ripening of ‘Guanhuahong’ pitaya (H. monacanthus). However, only HuMYB1 had R2 and R3 repeats with C1, C2, C3 and C4 motifs. HuMYB1 was localized exclusively to the nucleus and exhibited transcriptional inhibition capacities. Dual luciferase reporter assay demonstrated that HuMYB1 inhibited the expression of betalain-related genes: HuADH1, HuCYP76AD1-1 and HuDODA1. These results suggested that HuMYB1 is a potential repressor of betalain biosynthesis during pitaya fruit ripening. Our results provide the first genome-wide analyses of the R2R3-MYB subfamily involved in pitaya betalain biosynthesis and will facilitate functional analysis of this gene family in the future.